Excluding Miliusa velutina (Annonaceae) from Flora of China - Xue, Bine; Tan, Yun-Hong (Phytotaxa, 2016)
The Chinese specimens identified as Miliusa velutina were studied and they actually represent M. thorelii. The distribution range of M. velutina therefore does not include China. The name M. bannaensis is a synonym of M. thorelii and not M. cuneata as treated in Flora of China.